1997
DOI: 10.1021/ja9728839
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Protonation on the Structure, Stability, and Thermochemistry of Carbon-Centered Organic Radicals

Abstract: The effects of protonation on the geometries and stabilization energies of prototypical •CH2X radicals (X = NH2, OH, OCH3, PH2, SH, F, Cl, Br, CN, CHO, and NO2) have been studied with the use of ab initio molecular orbital calculations at the G2 level. The proton affinities at X of the •CH2X radicals and the analogous substituted methanes, CH3X, are compared and the corresponding heats of formation calculated. For π-donor substituents (X = NH2, OH, OCH3, PH2, SH, F, Cl and Br), protonation at X leads to consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 58 publications
4
62
1
Order By: Relevance
“…A pulsed high voltage of 1.2 kV was applied to the discharge electrodes attached to the nozzle. Because CH 2 Br is an open-shell molecule, Earth's magnetic field was canceled by using three sets of Helmholtz coils placed perpendicularly to one another.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pulsed high voltage of 1.2 kV was applied to the discharge electrodes attached to the nozzle. Because CH 2 Br is an open-shell molecule, Earth's magnetic field was canceled by using three sets of Helmholtz coils placed perpendicularly to one another.…”
Section: Methodsmentioning
confidence: 99%
“…Because theoretical calculations can be applied to any kind of molecule, including reactive species, systematic studies on the halogen-substituted methyl radicals have been reported. [1][2][3][4][5] The amount of experimental work on such substances, on the other hand, is rather limited, mostly because of the elusiveness of the radicals; however, when these radicals have been detected, the corresponding experimental results often serve as references to "calibrate" the method of calculation. 1 High-resolution spectroscopy is suitable for this purpose because it provides reliable and accurate molecular constants that can be used as reference values.…”
Section: Introductionmentioning
confidence: 99%
“…It should be remembered that the BAR rule was established for single bonds (Alcamí et al, 1990b), and therefore when π ‐type interactions are present a simple mechanism in terms of charge depletion or charge concentration does not hold. For example, for CH 3 X derivatives with π ‐acceptor substituents, such as CN, CHO, or NO 2 , protonation on X leads to a shortening of the CX bond (Mayer et al, 1997), because, besides the possible charge depletion of the bonding region, the hyperconjugative interaction of the substituent with π (CH 3 ) becomes enhanced. The theoretical results indicate that the second mechanism dominates and the bond shortens.…”
Section: Bond Weakening Versus Bond Reinforcement In Ion–moleculementioning
confidence: 99%
“…Thus, protonation removes the stabilizing effect of the lone pair leading to a very reactive electrophilic α-ammonio radical •CH 2 -NH 3 + with a negative radical stabilization energy. 10 In line with these ideas 5-exo cyclization of 11 (Scheme 4) afforded a very high yield of cyclized product 12 without any of the reduced ammonium salt 13. 14a In fact, this cyclization was too fast to allow measurement of the rate constant by the competition method, 15a and attempts at doing so by nanosecond LFP on appropriate substrates were also unsuccessful.…”
Section: Methodsmentioning
confidence: 71%
“…The α-aminomethyl radical (•CH 2 NH 2 ) has been studied in some detail 9 and is found to have a C-N bond with some π-character due to the ability of the amino group to delocalize the single electron into the nitrogen lone pair (Scheme 1). 9a As also shown in Scheme 1, the interaction between the single electron and the lone pair results in significant net stabilization, 10 thus, the relative ease of α-amino radical generation. Another consequence of delocalization is a rise in SOMO energy that makes this a very nucleophilic radical with a strong reducing character.…”
Section: Introductionmentioning
confidence: 84%